Takım çalışmalarında sürece ilişkin algı farklılıklarının verimlilik üzerine etkileri - Arsal, Eylem (My University, 2003)
Gelişen teknoloji, değişen iş akışları, farklı fonksiyonların bir arada çalışmasını zorunlu kılan projeler takım çalışmalarına olan eğilimi artırmış ve zamanla takımların yapılarını da bu gelişen ihtiyaçlara göre şekillendirmiştir. Bu nedenle bu araştırmada takım elemanlarının algı farklılıkları ile takımların verimliliği arasında bir ilişki olup olmadığını ve eğer varsa ilişkinin ne yönde gerçekleştiği araştırılmıştır. Araştırmada örgütün iklimini ölçen takım iklim envanteri ve kişilerin algı farklılıklarını ölçen ikinci bir ölçek kullanılmıştır. Araştırmanın sonucunda hipotezler kısmen doğrulanmış, bir kısmı anlamlı düzeyde açıklanamamış, daha geniş bir çalışma ile doğrulanabileceği varsayılmıştır. New technology, different workflows, projects that considers different functions should work together, has increased the demand of teams and the teams have been formed according to these demands. Because of this,this survey is about the different perceptions of team members and the relation of this perceptions with team productivity. In this study two different inventories have been used. The first one is team climate inventory to measure the team climate and to make estimations about the relation between different perceptions and team climate. The second one is much shorter one to find about the correlations between the independent variables. At the proved end of the study some hypothesis have been proved and some have been partially proved. These partially ones may be proved with a much wider survey.
Keywords: Örgütsel Davranış; Verimlilik